Audible Book Based on Pancasila Student Profiles as a Media for Introducing Quadrilaterals for Elementary School Students - Oktaviani, Cici; Rahayu Murti; Zeva Adi Fianto; Adam Aliathun Amin; Ulfiyani (Journal of Education Reseach and Evaluation, 2024)
Technological developments are spreading to all sectors, including education. As educators, we are required to utilize technology in learning, Many students have difficulty understanding geometric material, which is often presented in a conventional and less interesting way. On the other hand, education in Indonesia also aims to shape students' character in accordance with Pancasila values, such as mutual cooperation, integrity and independence. However, approaches that integrate character education with subject teaching are still limited. This research aims to analyze a mathematics audible book based on Pancasila student profiles that is feasible and practical as a medium for introducing rectangular flat shapes for fourth grade elementary school students by utilizing technological developments. The research uses the ADDIE model. The test subjects were fourth grade elementary school students, involving 94 students and 3 teachers. Data collection techniques through interviews and questionnaires. Data analysis uses the Aiken'v index. The results of the research show that overall the use of a mathematics audible book is feasible and practical as a medium for introducing rectangular shapes for class IV elementary school. The implications of this research are This book is designed to introduce the quadrilateral concept in an interesting way and in line with the Pancasila student profile, which emphasizes values ​​such as mutual cooperation, integrity and independence.